2009
DOI: 10.1007/s00239-009-9264-z
|View full text |Cite
|
Sign up to set email alerts
|

The Evolutionary History of the Structure of 5S Ribosomal RNA

Abstract: 5S rRNA is the smallest nucleic acid component of the large ribosomal subunit, contributing to ribosomal assembly, stability, and function. Despite being a model for the study of RNA structure and RNA-protein interactions, the evolution of this universally conserved molecule remains unclear. Here, we explore the history of the three-domain structure of 5S rRNA using phylogenetic trees that are reconstructed directly from molecular structure. A total of 46 structural characters describing the geometry of 666 5S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 87 publications
5
49
0
Order By: Relevance
“…Thus, the functional RNase P complex, originally thought a remnant of the ancient RNA world [Altman, 2009], appears to be a relatively recent evolving RNP ensemble. These results are noteworthy and are in line with an analysis of 5S rRNA and associated r-proteins that showed the existence of tight coevolution between proteins and nucleic acids in this small regulatory component of the ribosome [Sun and Caetano-Anollés, 2009]. …”
Section: Structural Phylogenomics Reveals a Coevolving World Of Protesupporting
confidence: 70%
See 1 more Smart Citation
“…Thus, the functional RNase P complex, originally thought a remnant of the ancient RNA world [Altman, 2009], appears to be a relatively recent evolving RNP ensemble. These results are noteworthy and are in line with an analysis of 5S rRNA and associated r-proteins that showed the existence of tight coevolution between proteins and nucleic acids in this small regulatory component of the ribosome [Sun and Caetano-Anollés, 2009]. …”
Section: Structural Phylogenomics Reveals a Coevolving World Of Protesupporting
confidence: 70%
“…Phylogenomic analyses also unfold the gradual evolutionary appearance of protein domains that are present in the viral and cellular world [Caetano-Anollés and Caetano-Anollés, 2003;Nasir et al, 2012]. Timelines of accretion of RNA structures [Caetano-Anollés, 2002] and protein domains were recently linked, showing tight coevolution between rRNA and r-proteins and an origin of the ensemble in ribosomal mechanics [Harish and CaetanoAnollés, 2012;Sun and Caetano-Anollés, 2009]. The evolutionary expansion of ribosomal structure by gradual accretion of both RNA helical structures and r-proteins is again incompatible with the RNA world-inspired hypothesis that the ribosome originated in the absence of proteins as a stand-alone biosynthetic ribozyme.…”
Section: The Rna World Hypothesis and Its Modern Contendersmentioning
confidence: 99%
“…3B) with exceptions in some positions due to SNP's. This lower accuracy in the 5S rRNA secondary structure prediction with respect to other RNA molecules has been reported previously 56 (and references therein). This could be due to possible interactions that are needed for the proper folding of the 5S rRNA.…”
Section: Evolutionsupporting
confidence: 50%
“…We have showcased this progression with proteins but expect nucleic acids will follow a similar progressive trend. In fact, we see the gradual formation of structure unfold for example in phylogenetic analysis of tRNA (Sun and Caetano-Anollés 2008b), RNase P RNA (Sun and Caetano-Anollés 2010), 5S RNA (Sun and Caetano-Anollés 2009), and the small and large subunits of rRNA (Harish and Caetano-Anollés 2011). We also reveal progressive growth in biological information.…”
Section: Discussionmentioning
confidence: 93%
“…A historical account of domain appearance ) matched rings of gene neighbors derived from an analysis of physical clustering of conserved genes in bacterial genomes (Danchin et al 2007). Furthermore, we have shown that the age of domains in ribosomal proteins coevolves tightly with the age of rRNA substructures, uncovering recruitment and accretion patterns, and revealing the relatively late molecular origins of the ribosome (Sun and Caetano-Anollés 2009;Harish and CaetanoAnollés 2011). Here, we focus on a historical account of domains defined at FF level and study the emergence of the most ancient molecular functions.…”
Section: Introductionmentioning
confidence: 97%